Electrochemical corrosion studies of spark plasma sintered zirconia particle-reinforced high-alloy steel at different temperatures. (January 2015) - Mandel, Marcel; Krüger, Lutz; Decker, Sabine
Highlights: Cyclic voltammetry was investigated on particle-reinforced steels at various T. The impedance response was analysed before and after the cyclic voltammetry. The corrosion kinetics were evaluated using different interface models. Pitting influences the corrosion kinetics stronger than the temperature. Film formation reduced the corrosion kinetics after cyclic voltammetry. Abstract: The influence of temperature on the corrosion behaviour of spark plasma sintered high-alloy steel – with particle reinforcement using 10 vol.% partially stabilised zirconia – was investigated. The cyclic polarisation behaviour and electrochemical impedance were analysed in a 5 wt.% sodium chloride solution. It was found that the corrosion potential was not influenced by temperature. However, the anodic polarisation behaviour and impedance exhibited significant declines in polarisation resistance when the temperature increased. A homogeneous corrosion attack was observed at 25 °C and 35 °C, while an intensified particle detachment and subsequent pitting corrosion occurred at 45 °C and 55 °C.